Cornelian Cherry Iridoid-Polyphenolic Extract Improves Mucosal Epithelial Barrier Integrity in Rat Experimental Colitis and Exerts Antimicrobial and Antiadhesive Activities In Vitro. (24th November 2020) - Szandruk-Bender, Marta; Rutkowska, Maria; Merwid-Ląd, Anna; Wiatrak, Benita; Szeląg, Adam; Dzimira, Stanisław; Sobieszczańska, Beata; Krzystek-Korpacka, Małgorzata; Kucharska, Alicja Z.; Matuszewska, Agnieszka; Nowak, Beata; Piórecki, Narcyz; et al.
Abstract : Background and Aims . Inflammatory bowel disease pharmacotherapy, despite substantial progress, is still not satisfactory for both patients and clinicians. In view of the chronic and relapsing disease course and not always effective treatment with adverse effects, attempts to search for new, more efficient, and safer substances are essential and reasonable. This study was designed to elucidate the impact of cornelian cherry iridoid-polyphenolic extract (CE) and loganic acid (LA) on adherent-invasive E . coli growth and adhesion in vitro and to assess the effect of pretreatment with CE or LA on the course of intestinal inflammation in rat experimental colitis compared with sulfasalazine. Methods . Antibacterial and antiadhesive activities of CE and LA were assessed using microdilution, Int407 cell adherence, and yeast agglutination assays. The colitis model was induced by 2, 4, 6-trinitrobenzenesulfonic acid. Studied substances were administered intragastrically for 16 days prior to colitis induction. Body weight loss; colon index; histological injuries; IL-23, IL-17, TNF- α, and chemerin levels; and STAT3, Muc2, and TFF3 mRNA expression were evaluated. Results . Only CE exerted antimicrobial and antiadhesive activities in vitro and alleviated colonic symptoms. CE coadministrated with sulfasalazine was more effective than single compounds in reversing increased concentrations of TNF- α, IL-17, and chemerin and decreased Muc2 mRNA expression. Conclusions . CE exerted a protective effect against experimental colitis via impaired mucosal epithelial barrier restoration and intestinal inflammatory response attenuation and given concomitantly with sulfasalazine counteracted colitis in a more effective way than sulfasalazine alone, which indicates their synergistic interaction. The beneficial effect of CE may also be due to its bacteriostatic and antiadhesive activities.